2013
DOI: 10.1007/s10856-013-4975-5
|View full text |Cite
|
Sign up to set email alerts
|

Pig dorsum model for examining impaired wound healing at the skin-implant interface of percutaneous devices

Abstract: Percutaneous medical devices are indispensable in contemporary clinical practice, but the associated incidence of low to moderate mortality infections represents a significant economic and personal cost to patients and healthcare providers. Percutaneous osseointegrated prosthetics also suffer from a similar risk of infection, limiting their clinical acceptance and usage in patients with limb loss. We hypothesized that transepidermal water loss management (TEWL) at the skin-implant interface may improve and mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 55 publications
3
19
0
Order By: Relevance
“…10 If the healing process is hampered by the ingress of bacteria into the tissue, it can lead to a localized infection of the implants, soft tissue damage, and ultimately implant failure. 11,12 This undesirable outcome brings overwhelming troubles for both clinicians and patients. 13 Therefore, it is imperative that a solution be found to functionalize percutaneous devices with anti-infection abilities.…”
Section: Introductionmentioning
confidence: 99%
“…10 If the healing process is hampered by the ingress of bacteria into the tissue, it can lead to a localized infection of the implants, soft tissue damage, and ultimately implant failure. 11,12 This undesirable outcome brings overwhelming troubles for both clinicians and patients. 13 Therefore, it is imperative that a solution be found to functionalize percutaneous devices with anti-infection abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Data have shown that the chronic inflammatory responses associated with the wound microenvironments were present at the skin/device interface regardless of implant indwelling time or animal model used . Further investigation of the periprosthetic interface with use of immunohistochemistry had revealed the presence of cytokeratin 6—commonly expressed by the migrating keratinocytes—and the presence of hypergranular tissue . These findings indicated a complex wound healing phenomenon and the presence of pro‐inflammatory responses at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…During cutaneous wound healing, epidermal cells at the wound edges, supported by the underlying granulation tissue, undergo proliferation and migration in order to cover the defect (Landen, Li, & Stahle, ; Werner, Krieg, & Smola, ). Around percutaneous devices, proliferation and migration of epidermal cells due to unresolved and ongoing wound healing may contribute to epidermal downgrowth (Holt et al, ; Iglhaut et al, ; von Recum, ). Thus, the histological characteristics observed in this study including the presence of a double epidermis and the granulation tissue, may provide evidence that the peri‐prosthetic epidermal tissue was in a state of continuous wound healing, which contributed to the observed downgrowth.…”
Section: Discussionmentioning
confidence: 99%